BUDAYA DAN BEHAVIOR INTENTION MAHASISWA DALAM MENILAI SERVICE QUALITY UNIVERSITAS KRISTEN PETRA - Edwin Japarianto (Institute of Research and Community Outreach - Petra Christian University, 2006)
The main objective of this research is to clarify a correlaition between culture and behavioral intention of Petra Christian University students, culture observed by the dimention of: Power Distance, Uncertenty Avoidance, Individualism, Masculinity dan Time Orientation. Bahavioral Intention observed by the dimention of: Loyalty, Propensity to Switch, Pay More, External Response dan Internal Response and service quality observed by the dimention of: tangible, Responsiveness, Reliability, Emphaty and Assurance. Using Path Analysis, the result of this research indicates that service quality can be measure by behavioral Intention where as culture can not be used as the basis a evaluation because cultureof the students tend to be uniform. Abstract in Bahasa Indonesia : Penelitian ini mencoba untuk menjelaskan hubungan budaya dan behavioral intention mahasiswa Universitas Kristen Petra (UK Petra) dalam menilai kualitas layanan jasa bidang akademik UK Petra. Budaya ditinjau dari Power Distance, Uncertenty Avoidance, Indivduialism, Masculinity dan Time Orientation. Behavioral Intention ditinjau dari Loyalty, Propensity to Switch, Pay More, External Response dan Internal Response sedangkan kualitas layanan ditinjau dari tangible, Responsiveness, Reliability, Emphaty and Assurance. Menggunakan Path Analysis, hasil penelitian menunjukkan kwalias layanan dapat dinilai melalui behavioral Intention sedangkan budaya tidak signifikan sebagai dasar penilaian karena cenderung seragam. Kata kunci: Budaya, Behavioral Intention, Kwalitas layanan.